ANALISIS PENGARUH IMPLEMENTASI MANAJEMEN KUALITAS TERHADAP KINERJA ORGANISASI PADA USAHA KECIL MENENGAH DI KOTA SALATIGA - Fitriana Ulfah; Susilo Toto Rahardjo (Faculty of Economics and Business Diponegoro University, 2013)
The research was inspired by Small and Medium Enterprises (SMEs) of food and beverage (F & B) industries which have not receive a certificate of SPP IRT from BPOM. The certificate is given to SMEs that have passed for quality test in production process. The objective of the research is to analyze influence of quality management implementation to SMEs’ organization performance which similar to Total Quality Management. The research was also a replication and modification of the previous research written by Salaheldin (2008). The object of the research was focus to SMEs of F & B industries in Salatiga, Central Java. This research was an empirical study by using the whole population called census technique in data collection. The data was obtained by distributing questionnaires to the 42 owners of SMEs or who were authorized to manage the SMEs above. Data analysis was performed by Structural Equation Model (SEM) with the PLS (Partial Least Square) Smart Software. The analysis of hypothesis showed that all of proposed hypothesis were accepted. The variables of Strategic, Tactical and Operational factor; had a positive and significant impact on Operational Performance, Financial Performance, and Non-Financial Performance. And the variable of Operational Performance had a positive and significant impact on Financial Performance and Non-Financial Performance. Key words: SMEs, Quality Management Practices, Operational Performance, OrganizationalPerformance